2013
DOI: 10.1371/journal.pone.0056948
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Membrane Insertion and Conductance Activity of the Metamorphic Chloride Intracellular Channel Protein CLIC1 by Cholesterol

Abstract: The Chloride Intracellular ion channel protein CLIC1 has the ability to spontaneously insert into lipid membranes from a soluble, globular state. The precise mechanism of how this occurs and what regulates this insertion is still largely unknown, although factors such as pH and redox environment are known contributors. In the current study, we demonstrate that the presence and concentration of cholesterol in the membrane regulates the spontaneous insertion of CLIC1 into the membrane as well as its ion channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(76 citation statements)
references
References 36 publications
6
69
0
Order By: Relevance
“…Moreover, to confirm the cholesterol-dependent nature of pyolysin we performed pre-experiments where PLO was pre-incubated with different amounts of cholesterol prior to its addition to tethered membranes. This approach had previously been used by others who had shown that pre-incubation with cholesterol blocked the dielectric damage inflicted to tethered membranes [30]. Our results clearly showed that cholesterol is acting as a potential binding or docking site for PLO, confirming the requirement of cholesterol for the activity of this toxin.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, to confirm the cholesterol-dependent nature of pyolysin we performed pre-experiments where PLO was pre-incubated with different amounts of cholesterol prior to its addition to tethered membranes. This approach had previously been used by others who had shown that pre-incubation with cholesterol blocked the dielectric damage inflicted to tethered membranes [30]. Our results clearly showed that cholesterol is acting as a potential binding or docking site for PLO, confirming the requirement of cholesterol for the activity of this toxin.…”
Section: Discussionsupporting
confidence: 80%
“…cholesterol, already performed in literature [30]. As seen in Figure 1D, pre-incubation of rPLO protein with cholesterol prior to its addition to membranes, resulted in dose-dependent abrogation of rPLO-induced dielectric damage to tBLMs.…”
Section: Electrochemical Impedance Of Tblms Is Affected By Rplomentioning
confidence: 52%
“…The CLIC proteins are redox sensitive and partition into lipid bilayers upon oxidation (Goodchild et al, 2009;Littler et al, 2005;Littler et al, 2004;Valenzuela et al, 2013), where they have ion-conducting properties that are blocked by IAA-94. Indeed, bovine CLIC5B (p64) was first isolated from kidney by affinity purification with IAA-94 (Landry et al, 1993;Redhead et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…This has allowed for their ease of study using a range of artificial lipid membrane systems including tip-dip and tethered bilayer membranes (tBLMs) [3,4]. Reported conductance levels from single channel recordings of the ion channel activity of recombinant CLIC1 (rCLIC1) added to artificial membrane systems and from cells over-expressing rCLIC have been varied [5,6].…”
Section: Introductionmentioning
confidence: 99%